Structural, thermomagnetic, and dielectric properties of Mn0.5Zn0.5Gd x Fe2−x O4 (x = 0, 0.025, 0.050, 0.075, and 0.1) - Lakshita Phor; Vinod Kumar (Journal of Advanced Ceramics, 2020)
Abstract In this paper, effect of Gd3+ was investigated on structural, magnetic, and dielectric properties of Mn0.5Zn0.5Gd x Fe2−x O4(x = 0, 0.025, 0.050, 0.075, and 0.1) nanoparticles prepared by facile coprecipitation method. X-ray diffraction (XRD) studies confirmed the single cubic spinel phase for all the samples and showed that lattice parameter (a exp) was found to increase from 8.414 to 8.446 Å with the substitution of Gd3+ ions due to their larger ionic radii than the replaced Fe3+ ions. Shape and size of developed nanoparticles were studied using transmission electron microscopy (TEM) and found that particle size decreased from 31.06 to 21.12 nm for x = 0–0.1. Magnetic properties showed that maximum magnetization decreased from 39.21 to 23.59 emu/g, and Curie temperature decreased from 192 to 176 °C with increase in x from 0 to 0.1 due to weakening of superexchange interaction. Dielectric parameters like dielectric constant (ε′ and ε″), dielectric loss (tanδ), AC conductivity (σ ac), and impedance (Z′ and Z″) as a function of frequency and composition were analyzed and discussed. It was found that ε′, ε″, σ ac, and tanδ values decreased with Gd substitution, which has been explained based on Maxwell-Wagner theory and hopping mechanism of electrons between Fe3+ and Fe2+ ions at octahedral sites. Nyquist plots for all the developed compositions showed single semi-circular arc which indicate the dominant effect of grain boundaries.